The Influence of Work Discipline and Work Environment on Teacher Work Performance at SMP Negeri 1 Lahat - Fitriadi, Heri (Indonesian Journal of Entrepreneurship and Startups, 2023)
This study aims to determine the effect of work discipline and the work environment both individually and collectively on the work performance of SMP Negeri 1 Lahat teachers. The population in this study were all teachers at SMP Negeri 1 Lahat, totaling 38 people. The sample in this study, namely all teachers working at SMP Negeri 1 Lahat, totaling 38 people, will be sampled in this study. So the method used in this study is the census method. The census method is a method by collecting data on the entire existing population. Testing the Effect of Work Discipline (X1) on Work Performance (Y) obtained a value of 0.003 <0.05, which means that the Work Discipline variable (X1) has a significant effect on Work Performance (Y). Testing the influence of the Work Environment (X2) on Work Performance (Y) obtained a Sig value of 0.000 <0.05, which means that the Work Environment variable (X2) has a significant effect on the Work Performance variable (Y). The calculation results show a significant value of 0.000 <0.05 then Ho is rejected and Ha is accepted, meaning that the variables of Work Discipline (X1) and Work Environment (X2). The coefficient of determination is 0.627, this means that the Work Discipline (X1) and Work Environment (X2) variables have a contribution to the Job Performance variable (Y) of 62.7% and the remaining 37.3% is influenced by other factors not examined by the author